Palladium-Catalysed Coupling and Acid-Mediated Cyclisation: Synthesis of Fluorenones and Fluorenes - Kumar, Devarapalli Ravi; Kishore, Dakoju Ravi; Satyanarayana, Gedu (SynOpen, 2018)
Palladium-catalysed sequential one-pot synthesis of fluorenones is described. The reaction comprises intermolecular Suzuki coupling and intramolecular acid-mediated cyclisation in a one-pot procedure. The protocol is also applied to the synthesis of fluorenes using a single column purification.
Keywords: Friedel–Crafts; cyclocarbonylation; fluorenone; fluorine